2022
DOI: 10.1371/journal.pone.0262685
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of NPK fertilizer on growth and nutrient accumulation in juniper (Juniperus procera) trees grown on fire-damaged and intact soils

Abstract: Wildfires significantly alter soil properties and result in vegetation shifts; therefore, rapid reforestation activities are needed in the forests affected by wildfires. The decreased nutrient in the soil is the obvious effect of wildfires; however, little is known about the reforestation of Juniper (Juniperus procera) forests with application of NPK fertilizers. Juniper forests are common in Asir and Taif regions of Saudi Arabia and vulnerable to wildfires; thus, reforestation is needed after the onset of fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The high correlation can be caused by dual terms: the properties of NPK compounds was more easily and quickly dissolves and the condition of the ASS ecosystem was acidic (pH 4.62-4.65). These two aspects support the rate of dissolution of NPK more intensively so that the N, P, and K content in NPK could readily and quickly dissolve [8,13] . This condition increases the content of N, P, and K in the soil.…”
Section: The Effect Of Npk On Some Chemical Properties Of Assmentioning
confidence: 71%
“…The high correlation can be caused by dual terms: the properties of NPK compounds was more easily and quickly dissolves and the condition of the ASS ecosystem was acidic (pH 4.62-4.65). These two aspects support the rate of dissolution of NPK more intensively so that the N, P, and K content in NPK could readily and quickly dissolve [8,13] . This condition increases the content of N, P, and K in the soil.…”
Section: The Effect Of Npk On Some Chemical Properties Of Assmentioning
confidence: 71%
“…Nitrogen (N), phosphorus (P), and potassium (K) are the three main essential nutrients that plants require for optimum growth and development. During the life cycle, an insufficiency of any of these nutrients has a deleterious impact on plant growth and development (Khalofah et al, 2022). N plays an important role in plants' vegetative growth, synthesis of chlorophyll, and subsequently in photosynthesis (Duarah et al, 2011;Khan et al, 2012).…”
Section: Effect Of Different N and Irrigation Scheduling On Nutrient ...mentioning
confidence: 99%
“…N plays an important role in plants' vegetative growth, synthesis of chlorophyll, and subsequently in photosynthesis (Duarah et al, 2011;Khan et al, 2012). P is involved in the released energy storage and transfer during photosynthetic activity, and its deficit delays plant maturity (Khalofah et al, 2022). In the current study, compared to the I 30 N 100-0 treatment, the I 45 N 50-50 treatment significantly (P<0.05) increased plant total N content by 38.6 and 35.51% in 2020-2021 and 2021-2022, respectively, and significantly (P<0.05) increased plant total K content by 21.…”
Section: Effect Of Different N and Irrigation Scheduling On Nutrient ...mentioning
confidence: 99%
“…It is assumed that planting trees in degraded lands could improve soil quality, enhance biodiversity, and provide ecosystem services (Masaba & Etemesi, 2021; Yirdaw et al, 2017). However, degraded lands have poor nutrients and this affects the growth and development of planted trees, which hinders afforestation activities (Khalofah et al, 2022). Many degraded soils are limited in their capacity to supply macro‐ and micronutrients (Kihara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While LeBel et al (2008) found that fertilizing increased the height of Picea mariana seedlings. Studies showed that increasing NPK doses significantly increased the growth of Juniperus procera grown on damaged and intact soils (Khalofah et al, 2022).…”
mentioning
confidence: 99%